Budaya Organisasi Dan Komitmen Organisasi Pengaruhnya Terhadap Employee Engagement (Studi pada Koperasi Pegawai Negeri Republik Indonesia Sumber Mulyo Tuban) - M. Alfi Faisal Rizza; Hadi Sunaryo; Muhammad Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to determine and analyze the influence of Organizational Culture and Organizational Commitment on Employee Engagement of members and administrators of KP-RI Sumber Mulyo Tuban. The population in the study were all members and administrators of KP-RI Sumber Mulyo Tuban. The sample used was all members and employees of KP-RI Sumber Mulyo Tuban. As for the sampling technique, if less than 100 is better taken all then this research is a census research.Based on the research results, it is known that the independent variables simultaneously affect the dependent variable, the value is known with a sig value below 0.05, then H1 is accepted, This means that the variables of Organizational Culture and Organizational Commitment have a simultaneous effect on Employee Engagement.Like the Organizational Culture variable, which is known to have a sig value below 0.05, it means that Organizational Culture has a partial effect on Employee Engagement. Organizational Commitment variable is known to have a sig value below 0.05, which means that the Job Satisfaction variable has a partial effect on Employee Engagement